Cost-effectiveness of the 13-valent Pneumococcal Conjugate Vaccine in Children in Portugal. Issue 8 (August 2017) - Gouveia, Miguel; Fiorentino, Francesca; Jesus, Gonçalo; Costa, João; Borges, Margarida
Abstract : Background: Pneumococcal infections are the leading cause of vaccine-preventable death in children. In June 2015, the 13-valent pneumococcal conjugate vaccine (PCV13) was introduced in the Portuguese Immunization Program. We evaluated the cost-effectiveness of children vaccinated with PCV13 versus no vaccination for preventing pneumococcal diseases. Methods: A cohort simulation model for 2014 Portuguese newborns was used, considering a lifetime horizon and existence of herd effect on adults. Model outcomes measured life years gained, direct and indirect healthcare costs and net benefits considering [Euro sign]20, 000 per life years gained. PCV13 clinical effectiveness rate by serotype covered was assumed similar to PCV7. Patients' resource use was based on 2014 diagnostic-related group database and experts' opinion, while national legislation and official drug cost database were the main sources for unitary costs. Univariate sensitivity analyses were conducted to assess results' effectiveness. Results: In base case scenario, PCV13 was a dominant strategy, being associated with better health outcomes and lower costs. In a lifetime, a total of 6238 infections (excluding acute otitis media) and 130 deaths were averted, with a total saving of [Euro sign]397, 217 ($432, 966). Net benefits were estimated above [Euro sign]28 million ($30 million). Results were robust in all sensitivity analyses, with positive net benefits, except when herd effect was excluded. Conclusions: Vaccination of children with PCV13 starting in their first year of life is a cost-effective intervention with the potential to save costs to the Portuguese health system and to provide health gains by reducing the burden of pneumococcal disease in the vaccines and through the herd effect of this vaccine.